Forward domain growth in 36° Y-cut congruent lithium niobate. (12th March 2019) - Neradovskaia, E. A.; Neradovskiy, M. M.; Esin, A. A.; Chuvakova, M. A.; Akhmatkhanov, A. R.; Baldi, P.; De Micheli, M. P.; Forget, N.; Shur, V. Ya.
Abstract: The domain growth during polarization reversal with small round liquid electrodes has been studied in 0.5-mm-thick 36° Y-cut congruent lithium niobate, which is of practical interest for high average power nonlinear frequency conversion of ultra-short laser pulses. Studying the polarization reversal in constant field, we analyzed the time dependence of the switched domains fraction to obtain the domain nucleation probability and determine the activation field equal to 42 kV/mm. Studying the polarization reversal in rising field, we observed linear field dependence of the forward domain growth velocity with a threshold of 30.3 kV/mm.